Invasif dan Persisten Pasteurella multocida Setelah Diinokulasi Secara Intratracheal pada Kalkun - Mahdi Abrar; Fakhrurrazi Fakhrurrazi (Universitas Syiah Kuala, 2010)
The objective of this study was to evaluate the invasiveness and persistence of Pasteurella multocida after intratracheal inoculation on turkeys. Four strains of Pasteurella multocida, P-1059, T-325, CU, and M-9 were used in this study and intratracheally (IT) inoculated into turkeys. The number of viable bacteria in the trachea, lung, liver, spleen, and the blood were enumerated during periods of 6 and 9 hrs post inoculation (PI). The result showed that four strains of organism were present in the organ and the tissues observed. In the liver, spleen, and blood, the virulent P-1059 strain showed significant increases within 6 or 9 hrs PI. Strain CU showed significant increase only in the spleen. Two other strains did not show significant increase in any organs; strain M-9, on the other hand, showed significant decrease in the trachea. These results indicated that P-1059 and three other strains showed their ability to invade the tissues or organs when they are intratracheally inoculated.